2018
DOI: 10.1111/ene.13613
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reference, emotion inhibition and somatosensory disturbance: preliminary investigation of network perturbations in conversion disorder

Abstract: These preliminary results of disturbances in brain networks related to memory, emotions and self-referential processing, and networks involved in motor planning and execution, suggest a role of these cognitive functions in the psychopathology of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
3
20
0
1
Order By: Relevance
“…Across the spectrum of motor FND (mFND), which we frame as encompassing functional [psychogenic nonepileptic/dissociative] seizures (FND‐seiz) and functional movement disorders (FND‐movt), distributed corticolimbic abnormalities spanning multiple brain networks have been identified (Baizabal‐Carvallo et al, 2019; Perez et al, 2015; Pick, Goldstein, et al, 2018; Szaflarski & LaFrance, 2018). Findings include heightened amygdala reactivity to affective stimuli (Aybek et al, 2015; Aybek, Nicholson, Zelaya, et al, 2014; Voon, Brezing, et al, 2010), increased limbic‐motor control network connectivity (Aybek et al, 2015; Aybek, Nicholson, Zelaya, et al, 2014; Diez, Ortiz‐Terán, et al, 2019; van der Kruijs et al, 2012; Voon, Brezing, et al, 2010), altered right temporoparietal junction (TPJ) activity and connectivity (Arthuis, Micoulaud‐Franchi, Bartolomei, McGonigal, & Guedj, 2014; Baek et al, 2017; Maurer et al, 2016; Voon, Gallea, et al, 2010), and default‐mode network abnormalities among other findings (Monsa, Peer, & Arzy, 2018). Structural MRI studies in mFND compared to healthy controls (HCs) also report increased amygdala gray matter volume (Maurer et al, 2018), cingulo‐insular atrophy (Labate et al, 2012; Perez, Williams, et al, 2017), and changes in sensorimotor and striatothalamic areas (Aybek et al, 2014; Bègue et al, 2019; Espay, Maloney, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Across the spectrum of motor FND (mFND), which we frame as encompassing functional [psychogenic nonepileptic/dissociative] seizures (FND‐seiz) and functional movement disorders (FND‐movt), distributed corticolimbic abnormalities spanning multiple brain networks have been identified (Baizabal‐Carvallo et al, 2019; Perez et al, 2015; Pick, Goldstein, et al, 2018; Szaflarski & LaFrance, 2018). Findings include heightened amygdala reactivity to affective stimuli (Aybek et al, 2015; Aybek, Nicholson, Zelaya, et al, 2014; Voon, Brezing, et al, 2010), increased limbic‐motor control network connectivity (Aybek et al, 2015; Aybek, Nicholson, Zelaya, et al, 2014; Diez, Ortiz‐Terán, et al, 2019; van der Kruijs et al, 2012; Voon, Brezing, et al, 2010), altered right temporoparietal junction (TPJ) activity and connectivity (Arthuis, Micoulaud‐Franchi, Bartolomei, McGonigal, & Guedj, 2014; Baek et al, 2017; Maurer et al, 2016; Voon, Gallea, et al, 2010), and default‐mode network abnormalities among other findings (Monsa, Peer, & Arzy, 2018). Structural MRI studies in mFND compared to healthy controls (HCs) also report increased amygdala gray matter volume (Maurer et al, 2018), cingulo‐insular atrophy (Labate et al, 2012; Perez, Williams, et al, 2017), and changes in sensorimotor and striatothalamic areas (Aybek et al, 2014; Bègue et al, 2019; Espay, Maloney, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of patients with functional seizures, Van der Kruijs et al 83 reported increased coactivation of the precuneus and cingulate gyri as compared to controls in the resting state and additionally found that, among patients, DMN RSFC strength was positively correlated with scores on dissociation questionnaires. Similarly, Monsa et al 82 found enhanced DMN RSFC in seven patients with unilateral functional paresis. In another study of unilateral functional paresis, De Lang et al 81 found failure of the vmPFC to deactivate during implicit motor imagery tasks corresponding to the affected limb.…”
Section: Mechanistic Models Of Fnds and Their Relevance To Psychedelimentioning
confidence: 76%
“…Several studies have reported abnormalities of DMN activity in patients with FNDs. [80][81][82][83] In a study of patients with functional seizures, Van der Kruijs et al 83 As mentioned previously, the DMN has been theorized to be the neurobiological correlate to the Freudian ego. In keeping with this model, increased DMN RSFC, and its downstream inhibition of limbic activity, has been proposed as the mechanistic underpinning for Freudian repression.…”
Section: The Default Mode Network and Neurobiological Correlates Ofmentioning
confidence: 97%
See 1 more Smart Citation
“…71 Furthermore, there were abnormalities in the functional connectivity within the default mode network, as well as between the default mode network and other areas/networks involved in memory, emotion, self-referential processing, motor planning and execution. 72 During movement, both patients with functional paresis and healthy controls feigning paresis showed smaller activation of the motor cortex contralateral to the affected limb. However, patients also showed a more widespread pattern of abnormal cortical activity.…”
Section: Functional Neuroimaging Biomarkersmentioning
confidence: 94%